Strangely rhetorical: composing differently with novelty devices - Butts, Jimmy, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Strangely Rhetorical establishes the groundwork for rhetorical strangeness as a lens under the broader interdisciplinary umbrella of rhetoric and composition and shares a series of rhetorical devices for practically thinking about how compositions are made unique. It explores how strange, novel, weird, and interesting texts work.--Provided by publisher.
What 1s Strangely Rhetorical? -- Why Strangene2s Matters -- How Strang3ness Works -- Where Is Str4ngeness? -- Se7en 5trangers -- Stran6er Relations -- Parrhesia: Why Speaking Plainly May Be the Strangest Trope of All.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Figures of speech; Literary style